2020
DOI: 10.1016/j.gore.2019.100519
|View full text |Cite
|
Sign up to set email alerts
|

A challenging case of twin pregnancy with complete hydatidiform mole and co-existing normal live fetus – A case report and review of the literature

Abstract: HighlightsTwin pregnancy with complete hydatidiform mole and co-existing normal live fetus is rare.Antenatal and postpartum complications such as gestational trophoblastic neoplasia are common.Patients require close clinical monitoring and urgent delivery in the setting of complications.Follow-up with serum β-HCG is important for the diagnosis of persistent trophoblastic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Gestational trophoblastic disease includes a large number of tumors that are interrelated, and with different propensities for local invasion and metastasis. Presenting as complete and partial hydatidiform mole, invasive mole, choriocarcinoma, placental site trophoblastic tumor, and epithelioid trophoblastic tumor [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational trophoblastic disease includes a large number of tumors that are interrelated, and with different propensities for local invasion and metastasis. Presenting as complete and partial hydatidiform mole, invasive mole, choriocarcinoma, placental site trophoblastic tumor, and epithelioid trophoblastic tumor [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The serious risks and complications that can occur during pregnancy, before and after delivery [5] require a timely differential diagnosis, providing the basis to proper management and follow-up. The objective of the present work is to describe a case of hydatidiform mole that coexists with alive and healthy fetus at birth in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Curry et al reported that only 64% (18 out of 24) of patients achieved spontaneous remission after hysterotomy, compared to 81% (243 out of 299) after suction evacuation [ 17 ]. More recently, use of abdominal hysterotomy for evacuation has been confined to case reports of coexistent mole and a live twin fetus, due to obstetric indications such as placenta previa, or prematurity and breech presentation, or HELLP Syndrome [ 18 , 19 , 20 ].…”
Section: Surgery For Hydatidiform Molementioning
confidence: 99%
“…Although largely unclear, the aetiology of gestational trophoblastic disease likely involves genetic abnormalities involved in fertilization. 1,2 Coexistent molar pregnancy with a normal fetus is a scarce situation, with most of the cases diagnosed antepartum by ultrasound findings of a complex, cystic placental component distinct from the fetoplacental unit. 3 It has an incidence of 1 in 22.000 to 100.000 pregnancieswith only about 200 cases reported in past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…4 Management of these cases is challenging due to the increased risk of antenatal and perinatal complications and the risk of developing gestational trophoblastic neoplasia after delivery. 2 It is essential to provide proper patient counselling regarding pregnancy continuation and alert for maternal and fetal risks.…”
Section: Introductionmentioning
confidence: 99%